2017
DOI: 10.4172/2376-127x.1000308
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fertilization Pregnancy is One of the Risk Factor for Atonic Bleeding in Problem-Free Pregnancy

Abstract: Background: To determine the risk factor for atonic bleeding in problem-free pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
2
Order By: Relevance
“…Our study found three times higher rate of severe PPH and blood transfusion in cesarean section in women with singleton pregnancies after IVF compared to spontaneous singleton pregnancies. We did not find such differences in vaginal births, in contrast to the results of some authors [22], who prove that IVF is a risk factor for abnormal postpartum hemorrhage in vaginal births.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found three times higher rate of severe PPH and blood transfusion in cesarean section in women with singleton pregnancies after IVF compared to spontaneous singleton pregnancies. We did not find such differences in vaginal births, in contrast to the results of some authors [22], who prove that IVF is a risk factor for abnormal postpartum hemorrhage in vaginal births.…”
Section: Discussioncontrasting
confidence: 99%
“…Inadequate contractility also affects perinatal bleeding [20]. There was no significant difference in bleeding during ECS between spontaneous and ARTI pregnancies in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…It has been reported that IVF/ICSI pregnancy can result in a high-risk delivery but the progression of pregnancy is normal [ 4 6 ]. IVF/ICSI pregnancy can increase the risk of postpartum hemorrhage [ 6 , 7 ]. The purpose of this study was to understand the reasons for the high risks in IVF/ICSI deliveries.…”
Section: Discussionmentioning
confidence: 99%